The influence of Russia's 2010/2011 wheat export ban on spatial market integration and transaction costs of grain markets - Miranda Svanidze; Linde Götz; Dmytro Serebrennikov (Applied Economic Perspectives and Policy, 2022)
Strong harvest shortfall and high world market prices prompted the Russian government to implement a wheat export ban in 2010 aiming to dampen domestic wheat prices. Building on regional price and trade data of Russia's wheat producing regions, we find strengthened domestic wheat market integration during the export ban period. Market integration decreased to its pre-ban level in the post-ban period; however, higher transaction costs resulting from increased risk of domestic grain trade during the export ban continued to prevail. Although market integration was temporarily strengthened, the export ban generally hampers market development in the long run.
Keywords: Q02; Q11; Q18; 330; export ban; regional market integration; Russia; TVECM; wheat